From Science Diplomacy to Education Diplomacy: the brazilian case - Ferreira, Gabriela Gomes Coelho (2020)
The use of soft power resources in smart strategies, has been usually linked by the literature with developed countries due to a perspective in which—especially—soft power is seen as an extension of hard power. However, Brazil, a developing country, has been signing Cultural Agreements since 1930s aiming to use science and education as diplomatic tools. This paper aims to give an historical perspective to the Brazilian science diplomacy through the signature of these bilateral cultural agreements since de 1930’s, and its development into education diplomacy in the 1960’s. We show in this paper that Brazil created a strong science diplomacy, embedded into its cultural diplomacy, by relying on the creation of a legitimate narrative based on culture, science and education as an alternative for its lack of hard power. These cultural agreements were developed into national exchange programmes focusing mainly on higher education students since 1965, and they exist still nowadays—as one of the world longest science (and education) diplomacy strategies of its kind, creating a successful and steady foreign policy managed by the Brazilian diplomatic body.